Komparasi Ketahanan Erosi dan Korosi pada Coating Hidrofobik Sol-Gel dan Silika-PDMS untuk Logam Alloy - Putra, I Gede Gilang Taruna; Aritonang, Sovian (Fakultas Teknik UMSU, 2025)
Corrosion in metal alloys such as aluminum and carbon steel poses a major challenge in industries like aerospace, marine, and automotive, where such materials are frequently exposed to harsh environments. Hydrophobic coatings have emerged as promising solutions to enhance corrosion resistance. Among them, sol-gel and silica-PDMS coatings stand out due to their specific advantages. Sol-gel coatings are known for their excellent corrosion and erosion resistance, strong adhesion, and high mechanical durability, making them suitable for aggressive environments. On the other hand, silica-PDMS coatings provide superior hydrophobicity, ease of application, and flexibility, though with moderate corrosion resistance. This paper compares the performance of both coatings in terms of their corrosion and erosion resistance, application methods, and environmental suitability. The findings indicate that sol-gel coatings outperform silica-PDMS coatings in corrosion and erosion resistance, while silica-PDMS is more favorable for applications requiring high water repellency but in less corrosive conditions. Future research is recommended to optimize the formulation of both coatings and investigate hybrid solutions that combine the strengths of each material.